(3JbfjGJ GdeMGSHI (B/s - (3NGa QHj, eMeO GdRfs ((3GdLRGFQ(B: s (3OGQ GHf QTOddfTQ hGdJhRjY(B, s, 2002)
1- (3GdeDSSI (B2- (3GdejRGfjI hJZjQGJgG (B3- (3GdfJjLI hGdejRGfjGJ (B3- (3GdMSGH MSGHGJ GdGUhd (B4- (3MSGHGJ GdNUhe (B5- (3GdfJGFL (B6- (3GdYbO GdeROhL hGdMSGHGJ GdebGHdI GdjhejI (B7- (3GdJMhjd (B8- (3MSGHGJ GdfbOjI (B9- (3YedjGJ GdTQGA hGdHjY aj GdeDSSGJ GdUfGYjI (B10- (3YedjGJ GdTQGA hGdHjY eY GdJNajVGJs
Keywords: (3JbfjGJ eMGSHIs